Preparation of Amidoxime Polyacrylonitrile Nanofibrous Membranes and Their Applications in Enzymatic Membrane Reactor. Issue 2 (June 2014) - Feng, Quan; Wei, Qufu; Hou, Dayin; Bi, Songmei; Wei, Anfang; Xu, Xiuzhen
Ployacrylonitrile (PAN) nanofibers were formed by electrospinning. Amidoxime polyacryonitrile (AOPAN) nanofibrous membranes were formed by reaction between PAN nanofibrous membranes and hydroxylamine hydrochloride, and Fe(III)-AOPAN metal chelated nanofibrous membranes were prepared for immobilizing catalases. The enzymatic membrane reactor (EMR) with immobilized catalases was assembled, and the fluxes of membrane and conversion ratio of EMR were studied. The immobilized catalases showed better resistance to pH and temperature change than that of the free form, and the storage stabilities of immobilized catalases were higher than that of the free catalases. The flux of the membrane and the conversion ratio of EMR were calculated, and the reusability of the EMR was studied. The results of experiments show that the immobilized catalases had a high affinity with the nanofibers, and the EMR has excellent performance.